Constructing the FEEM sustainability index: A Choquet-integral application - Caterina Cruciani; Silvio Giove; Mehmet Pinar; Matteo Sostero (Fondazione Eni Enrico Mattei (FEEM), 2013)
This paper presents an application of a multi-attribute aggregation methodology to the construction of a sustainability index. Sustainability is a multi-faceted issue, in which synergies or conflicts may arise among the different components, thus making it a complex concept to which multi attribute methods can be employed. This paper addresses the development of the FEEM Sustainability Index (FEEM SI), a composite index including 19 different indicators grouped in the three classical pillars of sustainability ? economic, social and environmental. We present the relevance of multi-attribute aggregation methodologies when dealing with such complex concepts and provide an aggregation methodology used for this case study, the Choquet-integral aggregation. First, we normalize each sustainability indicator with the use of a benchmarking procedure with a smooth target of sustainability. Furthermore, an ad-hoc questionnaire implemented to assess the importance of each sustainability indicator and their interaction with other indicators through expert elicitation. After normalizing each sustainability indicator and computing consensus importance of each sustainability indicator and their interactions for the Choquet-integral aggregation procedure, the overall sustainability index, the FEEM SI is calculated. This paper also conducts robustness analysis and discusses the main implications of the aggregation methodology used.
Keywords: C43; C44; Q01; Q56; 330; sustainability indices; composite indicators; Choquet integral; multiattribute value theory